KERUGIAN EKONOMI DAN MANAJEMEN PENGENDALIAN SERANGAN LALAT BUAH PADA KOMODITAS HORTIKULTURA DI INDONESIA (Forum Penelitian Agro Ekonomi, 2023)
One of the main obstacles to increasing fruit and vegetable production in Indonesia is the attack of fruit flies. These pests can cause significant damage to fruits and vegetables and pose a severe threat due to their destructive power and quarantine implications, resulting in export bottlenecks. This paper is a literature review to identify the types of fruit flies and their hosts, the economic losses caused by fruit flies, and the government's program for controlling fruit flies in Indonesia. The results show that many fruit flies negatively influence horticultural crops. Fruit flies can cause damage to 150 species of fruit and vegetable crops, both in tropical and subtropical regions. Bactrocera (Diptera: Tephtritidae), a tropical fruit fly genus, is the most common type of fruit fly that attacks fruits and vegetables in Indonesia. The damage level of the fruit fly attack is about 13.5–70%. Specifically for mangoes, the damage is about 30%. Several methods can be applied to overcome fruit flies, whether manually, physically, biologically, or through an integrated approach. An area-wide integrated fruit fly management method may be the best option for fruit fly control effectiveness.
Keywords: area-wide management; fruit; integrated pest management; vegetable; buah-buahan; pengelolaan hama penyakit terpadu; pengelolaan skala luas; sayuran